ANALISIS PEMASARAN USAHATANI TOMAT DI DESA NUPABOMBA KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Sucita, Reski; Tangkesalu, Dance; Lamusa, Arifuddin (AGROTEKBIS, 2017)
The aim of this research is to know the shape of tomato marketing channel, the amount of margin in each marketing channel, the price part received by the farmer in each marketing channel and the marketing efficiency of tomatoes in each marketing channel. The analysis showed that the marketing margin tomatoes were obtained for the 1 channel IDR 1,000 / Kg and channel 2 which is IDR 1,500 / Kg. The part of the price received by farmers in the channel 1 is 60.00%, and the second channel at 70.00%. Thus, the greatest part of the price received by farmers is on channel 2. Tomato marketing channels in Nupabomba village consists of two channels, namely: 1) Farmers â Trader Gatherer â Trader Retailer â Consumer, 2) Farmers â Traders Retailer â Consumer. In the first channel, part of the price received by farmers amounted to 60.00% efficiency value was 40.00%. On channel 2, section prices received by farmers amounted to 70.00% of the value of efficiency is 30.00%, resulting in more efficient marketing channel is the channel 2.Â Keywords: Efficiency, marketing, margin,tomato.